Sistem Kearsipan Surat Berbasis Web Pada Biro ISDA Sekretariat Daerah Provinsi Jateng - Rediza Arya Dilla; Isworo Nugroho (LPPM STIKOM Tunas Bangsa, 2023)
The Infrastructure and Natural Resources Bureau at the Central Java Regional Secretariat has a role in coordinating the preparation of regional policies, coordinating the implementation of regional apparatus tasks, monitoring and evaluating the implementation of regional policies, providing administrative services and developing ASN Resources in several fields. However, the management of letters at the ISDA Bureau is still done manually and involves a lot of paper to be filled out in order to schedule letters according to their grouping. With so much paper used, this raises several obstacles such as the need for large storage space, security risks from stored letters, and the length of time it takes to search for letters. Guided by this problem, the author tries to make a letter archiving information system program with a design method using the UML method, analysis and system design with the Unified Modeling Language. In making this application using PHP MySQL as a database management system. The final result of this research is in the form of a website-based application to make it easier for administrative staff to file letters.